THE INFLUENCE OF ACCOUNTING INFORMATION SYSTEM, EMPLOYEE DISCIPLINE, AND ORGANIZATIONAL CULTURE ON ACCOUNTING INFORMATION QUALITY - Nara Ika Prayendra; Rapina Rapina; Tan Ming Kuang; Johannes Buntoro Darmasetiawan (ACCRUALS (Accounting Research Journal of Sutaatmadja), 2026)
The development of accounting information systems in the era of technology and globalization is expected to improve the quality of accounting information. Moreover, the implementation of supporting work discipline and an organizational culture aimed at enhancing the quality of the resulting accounting information is also anticipated. However, in reality, the quality of accounting information produced, particularly within the government, remains relatively low. Previous research has examined the impact of various variables on the quality of accounting information systems. This study is conducted with the aim and novelty of determining the influence of accounting information systems, employee discipline, and organizational culture on the quality of accounting information. This type of research is quantitative, with the sample obtained using primary data through the distribution of questionnaires to employees in the accounting, finance, and tax departments of private companies, amounting to 80 respondents. The sampling technique in this study employs purposive sampling with the Structural Equation Model (SEM) research model. Data analysis utilizes SmartPLS. The results of the study indicate that the accounting information system does not significantly influence the quality of accounting information, whereas employee discipline and organizational culture have a significant effect on the quality of accounting information. With these findings, it is hoped that future research can use a larger data sample to achieve significant results and assist in the generalization of research findings. This study suggests that companies focus on improving discipline through training, supervision, and reward systems that support adherence to accounting procedures. Strengthening an organizational culture that emphasizes work discipline can also improve the quality of accounting information